The European venture capital landscape: an EIF perspective. Volume I: The impact of EIF on the VC ecosystem - Helmut Kraemer-Eis; Simone Signore; Dario Prencipe (European Investment Fund (EIF), 2016)
In the past 20 years, the European Investment Fund (EIF, the Fund) has been the leading public provider of risk capital, and in particular of venture capital (VC), to young and innovative European startups. VC is an essential source for startups to achieve growth and create value through innovation, and although it should not be seen as a substitute to traditional banking finance (since it serves only a specific and restricted class of firms), research has shown that the innovativeness, productivity and development of the overall economy reap the returns of a thriving venture capital ecosystem. EIF's established reputation in the European VC market is substantiated by its significant role in European investment and fundraising activity. In this paper we estimate that the investment activity backed by EIF represented 41% of total investments in Europe in 2014 (29% in 2007). The share directly attributable to EIF amounts to 10% (5% in 2007), hinting to the significant leverage that characterises EIF-backed investments. Moreover we estimate that fundraising volumes backed by EIF in 2014 amount to 45% of the overall volumes collected by European VC investors (36% in 2007), against a share directly attributable to EIF totalling 12% (5% in 2007)...
Keywords: 330